A randomized clinical trial of hyaluronic acid gel pulpotomy in primary molars with 1 year follow-up - MENTEŞ, ALİ RECAİ (TAYLOR & FRANCIS LTD, 2022)
Objective This randomized clinical study aimed to evaluate the success of hyaluronic acid (HA) as a pulpotomy medicament of human primary molars and to compare it with formocresol (FC) and ferric sulphate (FS) pulpotomy treatments up to 12 months. Materials and methods The study was conducted with 130 primary molars of 44 children. The ethical approval and registration to clinical trials (No: NCT04115358) were completed. After the removal of all the coronal pulp tissue, a 0.5% HA gel, or a FC, or a 20% FS solution were applied randomly to the radicular pulp tissues of the primary molars. Then, the pulp chambers were filled with a zinc oxide eugenol cement and restored either with a composite filling material or with a stainless-steel crown. The treatment success rates of the 3 groups were followed and compared clinically and radiographically at 1st-, 3rd-, 6th- and 12th-months. Results Primary molars treated with FC, FS and HA dressings were clinically successful 77.5%, 86.8% and 87.5% respectively after 12th-month follow-up (p > .05). Radiographic successes of FC, FS and HA groups were lower than clinical successes (57.6%, 68.8%, 57.9% respectively at the 12th-month) but the difference between the groups was not statistically significant (p > .05). Equivalence analysis assuming not more than 10% difference between the materials suggested that HA was not inferior to FC or FS. Conclusions Within the limitations of this study, our randomized clinical trial shows that HA is a promising pulpotomy medicament in primary molars. However, further studies are justified to further improve the HA material success.
Keywords: Formocresol; ferric sulphate; hyaluronic acid; paediatric endodontics; vital pulp therapies; MINERAL TRIOXIDE AGGREGATE; FERRIC SULFATE; FORMOCRESOL; 3MIXTATIN; MTA